Sophoridine Derivatives Induce Apoptosis and Autophagy to Suppress the Growth of Triple‐Negative Breast Cancer through Inhibition of mTOR Signaling. (12th October 2021) - Dai, Linlin; Wang, Luyao; Tan, Cheng; Cai, Jun; Shen, Hongsheng; Zhang, Ting; Zhi, Shuang; Yang, Zibo; Hu, Yunhui; Zhao, Xiumei; Li, Dongdong
Abstract: In order to improve the antitumor potency and therapeutic margins of natural product sophoridine, its novel nitrogen mustard carbamate derivatives were designed and synthesized. In screening their in vitro activity, we found all the tested compounds were more potent against the highly aggressive triple‐negative breast cancer cell line MDA‐MB‐231. Cellular functional assays showed that representative compounds could induce G1‐phase arrest and trigger apoptosis, evidenced by the alteration of Bax, Bcl‐2, caspase‐3 and PARP levels. Furthermore, these compounds significantly enhanced the autophagic flux with increased expression of LC3‐II and Beclin‐1, as well as decreased level of p62, which may attribute to simultaneously inhibition of the phosphorylation of p70S6K, 4E‐BP1 and AKT, the key substrates of the mTOR signaling pathway. In vivo, two compounds revealed potent antitumor activity in mice bearing MDA‐MB‐231. Altogether, our work describes novel leads to yield more potent chemotherapeutics against triple‐negative breast cancers, possibly mesenchymal stem‐like subtype. Abstract : To improve the antitumor potency and therapeutic margins of the natural product sophoridine, novel nitrogen mustard carbamate derivatives were synthesized. We found all the tested compounds to be more potent against the triple‐negative breast cancer cell line MDA‐MB‐231. Altogether, our work describes new leads to yield more potent chemotherapeutics against triple‐negative breast cancers, possibly mesenchymal stem‐like subtype.